Wound Healing Effect of a Topical Product from Ajuga chamaecistus ssp. tomentella in Pressure Ulcer: a Randomized Double-Blind Placebo-Controlled Clinical Trial - Mohsen Adib; Mohammad Hossein Jarrahzadeh; Tayebeh Toliyat; Laila Shirbeigi; Nafiseh Khosravi Dehaghi; Seyede Nargess Sadati Lamardi* (Iranian Society of Pharmacognosy, 2024)
Background and objectives: Ajuga genus is used as wound healing in traditional Persian medicine. This study aimed to evaluate the effectiveness of Ajuga chamaecistus ssp. tomentella ointment on healing pressure ulcers in patients admitted to the intensive care unit. Methods: In this randomized, double-blind, placebo-controlled clinical trial, 131 patients with grade 1 or 2 pressure ulcers were randomly assigned into one of two groups through simple randomization. The study group received 3% Ajuga ointment, containing 17.26 µg/mL of 20-hydroxyecdysone (ecdysterone) as the main compound, while the control group received placebo twice a day for 14 days in addition to the standard care for pressure ulcers Changes in the degree and size of wounds were considered as the primary outcomes of the study based on the 2-digit Stirling scale. Results: Forty patients in each group completed the research. Mean (95% confidence interval) difference values, for wound degree, between two groups on day 7 vs. day 0 was -0.88 (-1.01 to -0.76, p<0.001), and on day 14 vs. day 0 was -1.57 (-1.78 to -1.36, p<0.001). Mean (95% confidence interval) difference values, for wound area, between two groups on day 7 vs. day 0 was -1.730(-1.979 to -1.48, p<0.001), and on day 14 vs. day 0 was -3.142(-3.563 to -2.72, p<0.001).Conclusion: Topical application of Ajuga ointment significantly improved pressure ulcers  on days 7 and 14 compared to placebo. Evaluation of the effects of this plant on a larger sample size, for a longer period of time and in different medical centers is recommended.